AVIATION DIPLOMACY IN SOUTHEAST ASIA - Indriani, Mutiara (Journal of Social Political Sciences, 2021)
Globally, the COVID-19 pandemic brought a wave of economic decline to the aviation industry due to disruptions in the supply and demand chain. With a population of 650 million, ASEAN governments are obliged to support the recovery process following the negative impacts of the COVID-19 pandemic. While the aviation industry is opening up, an approach that is inclusive and appealing to the public to complement safety policy and liquidity support is necessary for the aviation industry. This research attempts to gain a deeper understanding of how aviation diplomacy could play a role in the regional connectivity agenda amid the rising importance of international aviation. This research proposes that aviation subjects as diplomatic actors are engaged in the diplomatic process, whereas in the context of soft power and multistakeholder diplomacy concept, the ASEAN government and airlines are drivers of regional connectivity. By employing qualitative methods with inductive logical thinking as the analysis framework, this research shows that air assets and air infrastructures are meaningful in three different ways; raising national and regional identity awareness, building political ties, and ensuring cross-border mobility. Thus, ASEAN governments shall continue to support the aviation industry and utilize aviation diplomacy as a soft power approach in the region.